Food and the Urgency of Now - Concannon, Kevin (Maine Policy Review, 2011)
Kevin W. Concannon, undersecretary for food and nutrition services in the U.S. Department of Agriculture, discusses the necessity for food and nutrition programs, both because of the increase in hunger in the country and because of the rise in obesity. He notes that the focus on local and healthier foods is important in addressing both hunger and poor nutrition.